Os trilhos da memória: o bonde de Belém, a História soterrada por calcário e argila? - SILVA, Breno Ednan Pacifico da (2022)
The present article reports how was the process of Conselheiro João Alfredo Street in the city of Belém do Pará, during its existence until the case of soterramento of part of the street by a concrete walkway, going through some of the history of the history of this street, especially the tramway object, which was characteristic in social and spatial configurations of the street. Bringing a central point from the case of burial, the history of the street was buried ? which seeks in oral research elucidations on this issue in the present society of that street, thus the article is structured in points from the history of the street, history of the streetcar, revitalizations and planning that the street had to its recent case of burial in 2020, thus being done and using for construction oral and documentary sources and structured by the qualitative approach.